Care and the Sustainability of Life: Contributions from Collective Practice for Rethinking the Socio-Environmental from an Interdependent Perspective - Arce Pimienta, Marla (2026)
This article aims to present a series of contributions to the conceptual discussions currently taking place around care and its multidimension, which are closely related between the theoretical approaches of the latter and the collective responses to the widespread socio-environmental crisis. Likewise, starting from the term of interdependence, the discussion of care is completed by proposing an integrated reading of three dimensions: self-care, collective care and care for the territory and nature. Methodology: To get there, the conceptual discussion is resumed, especially that which is taking place in Latin America and the global South, as well as the reflections and experiences shared during the period of 2023 and 2024 with collectives and organizations that militate in Mexico City around the defense and support of life. The result of such exchanges, both theoretical and in political practice; notes that the fact that the multiple dimensions of care are read in an interdependent key is being central to thinking and reconfiguring political action both individually and collectively in the face of challenges brought about by the widespread socio-environmental crisis and alternatives to it.